Apium extract alleviates indomethacin-induced gastric ulcers in rats via modulating the VEGF and IK-κB/NF-κB p65 signaling pathway: insights from in silico and in vivo investigations - Dalia H. Abu-Baih; Alshymaa Abdel-Rahman Gomaa; Nada Mohamed Abdel-Wahab; Enas Reda Abdelaleem; Azza M. Abdel Zaher; Noha F. Hassan; Gerhard Bringmann; Usama Ramadan Abdelmohsen; Faisal H. Altemani; Naseh A. Algehainy; Fatma Alzahraa Mokhtar; Miada F. Abdelwahab (BMC, 2024)
Abstract Background Gastric ulcers represent a worldwide health problem, characterized by erosions that affect the mucous membrane of the stomach and may even reach the muscular layer, leading to serious complications. Numerous natural products have been assessed as anti-ulcerogenic agents, and have been considered as new approaches for treatment or prevention of gastric ulcers. The present research investigated the preventive benefits of Apium graveolens L. (Apiaceae), known as celery, seed extract towards indomethacin-induced ulceration of the stomach in rats. Methods Metabolomic profiling, employing liquid chromatography coupled to high-resolution electrospray ionization mass spectrometry (LC-HR-ESI-MS), was implemented with the aim of investigating the chemical profile of the seeds. Histopathological analysis of gastric tissues, as well as assessment of numerous inflammatory cytokines and oxidative stress indicators, confirmed the in vivo evaluation. Results The prior treatment with A. graveolens seed extract resulted in a substantial reduction in the ulcer index when compared to the indomethacin group, indicating an improvement in stomach mucosal injury. Moreover, the gastroprotective effect was demonstrated through examination of the oxidative stress biomarkers which was significantly attenuated upon pre-treatment with A. graveolens seed extract. Vascular endothelial growth factor (VEGF), a fundamental angiogenic factor that stimulates angiogenesis, was markedly inhibited by indomethacin. A. graveolens seed extract restored this diminished level of VEGF. The dramatic reductions in NF-κB protein levels indicate a considerable attenuation of the indomethacin-induced IKκB/NF-κB p65 signaling cascade. These activities were also correlated to the tentatively featured secondary metabolites including, phenolic acids, coumarins and flavonoids, previously evidenced to exert potent anti-inflammatory and antioxidant activities. According to our network pharmacology study, the identified metabolites annotated 379 unique genes, among which only 17 genes were related to gastric ulcer. The PTGS2, MMP2 and PTGS1 were the top annotated genes related to gastric ulcer. The top biological pathway was the VEGF signaling pathway. Conclusion A. graveolens seed extract possesses significant anti-ulcer activity, similar to famotidine, against gastric lesions induced by indomethacin in rats. It is worth highlighting that the extract overcomes the negative effects of conventional chemical anti-secretory drugs because it does not lower stomach acidity.